Desvendando o corpo humano : corpo e saúde como unidade didática na educação física escolar - Santos, Hemerson Lowe dos (2024)
The present research was proposed and developed within the scope of the Professional Master's Program in Physical Education (PROEF) at UFMT, focusing on the development and implementation of a pedagogical intervention related to the body and health as a didactic unit in school Physical Education for the 1st year of high school at Escola Estadual Dom Pedro II 2nd Lt. BM Kleiber Rodrigues Alves, in the municipality of Colíder - MT. The general objective was to understand the meanings attributed by high school students to the didactic unit "Body and Health." The specific objectives were: to identify the meanings and social representations attributed by high school students regarding the body and health; to provide opportunities for reflections on the concept of expanded health and its determinants for physical, mental, and social well-being; to develop and implement a didactic unit related to body and health with high school students; to analyze the experiences and perceptions of high school students regarding the didactic unit "Body and Health." The research follows a qualitative approach, anchored in the procedures and assumptions of pedagogical intervention research, divided into two distinct stages. Stage 1: "The Intervention Method" focused on constructing data collection instruments (diagnostic entry and exit questionnaires and an observation guide) and developing the theoretical framework on the subject. Both the theoretical framework and the entry diagnostic questionnaire contributed to the design and implementation of the didactic unit. Stage 2: "The Intervention Evaluation Method" utilized information from the research instruments developed in the first stage, as well as data from the implementation of the unit, based on the empirical experience of the teacher researcher, observations recorded in the observation guide, and photographic records. The aim was to analyze and assess the results of the pedagogical intervention related to the didactic unit "Body and Health" under the concept of "Expanded Health." Through the construction of the theoretical framework, we observed that Physical Education is not guaranteed as a mandatory curricular component in the new high school curriculum. Although some official curricular documents in the field advocate for a broad perspective on "health," there is a lack of didactic materials and concrete guidelines to assist teachers in developing the concept of "Expanded Health." In summary, both during the implementation and in the analysis of the effects of the didactic unit "Body and Health," it was possible to provide students with the opportunity to develop analytical and reflective skills regarding information disseminated in the media about beauty and health standards, under the lens of the "Expanded Health" concept. This enabled them to make more conscious and responsible decisions regarding self-care and collective health. It is hoped that this study serves as an initial step for teachers and researchers to promote the concept of "Expanded Health" in schools and scientific conferences, thereby contributing to breaking the biological constraints that still permeate topics related to "Body and Health." Additionally, this research aims to encourage new perspectives and conceptions that have not yet been explored under the lens of Expanded Health.